Planta de transformación frutícola: Plan parcial de manufacturación frutícola 2030 Mosquera (2016)
The partial plan frutícola manufacturing (Mosquera), tying find a way to solve this problem that presents the region generating which in turn operate as a cluster stockpiled part of the fruit entering the capital of the logistics platform county preventing the entry of this burden and in turn easing much of the western entrance and exit, giving an added value that generals income to the region and the development of industries that generate opportunities for people.